2008
DOI: 10.1002/jmri.21412
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lymph node metastasis in cervical and uterine cancers by diffusion‐weighted magnetic resonance imaging at 3T

Abstract: Purpose:To evaluate diffusion-weighted imaging (DWI) for detection of pelvic lymph node metastasis in patients with cervical and uterine cancers. Materials and Methods:Fifty patients scheduled for pelvic lymph node dissection were enrolled for 3T magnetic resonance imaging (MRI) using a single-shot echo-planar DWI technique, body-phased array coil, b ϭ 0, 1000 s/mm 2 . We measured short/long-axis diameters, mean apparent diffusion coefficient (ADC) values of all identifiable nodes, relative ADC values between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
113
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(122 citation statements)
references
References 14 publications
6
113
2
1
Order By: Relevance
“…Other studies have also evaluated the accuracy of DW-MRI in assessment of myometrial invasion [20][21][22] and have shown similar results. Shen at al.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Other studies have also evaluated the accuracy of DW-MRI in assessment of myometrial invasion [20][21][22] and have shown similar results. Shen at al.…”
mentioning
confidence: 68%
“…Improvements in sensitivity have been reported at 3 T by Lin et al [22]. In patients with cervical or uterine cancer, they found that a combination of nodal size and the relative tumour to node ADC resulted in an increase in sensitivity compared with size criteria from 25 to 83%, whilst maintaining very high specificities.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Because ADC values vary according to numerous factors, such as MR acquisition parameters and magnetic field, the use of relative ADC can improve the diagnostic accuracy of DWI for detecting metastatic lymph nodes (130-132). Lin et al (132) found that the combination of size and relative ADC values resulted in better sensitivity (25% vs. 83%) and similar specificity (98% vs. 99%) compared with conventional MRI. Primary tumor type (adenocarcinoma vs. adenosquamous carcinoma), focal infiltration with micrometastasis and associated necrosis also affect ADC values, and overlap between hyperplastic and metastatic lymph nodes could occur (119,(129)(130)(131)(132)(133)(134).…”
Section: Female Pelvis Applicationsmentioning
confidence: 99%
“…These modalities include diffusion-weighted imaging (DWI) of MRI, MRI with ultrasmall superparamagnetic iron oxide (USPIO) [13,21,22] , and positron emission tomography and CT (PET/CT) using 18 F-fluorodeoxyglucose (FDG). To date, there have been three reports on apparent diffusion coefficient (ADC) obtained with DWI for the detection of LN metastasis [23][24][25] and several on PET/CT [20,[26][27][28][29][30][31] for uterine cancer. To the best of our knowledge, there have been no studies comparing the diagnostic accuracy of DWI and PET/CT for preoperative evaluation of LNs in patients with uterine cancer.…”
Section: Introductionmentioning
confidence: 99%